Becoming a Poet: A Narrative Analysis in Predicting Schwartz's Values in the Artist Acep Zamzam Noor - Diya Bulan Farida; Mirra Noor Milla (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
Acep Zamzam Noor, a renowned artist from West Java known for his works in painting and literature, is now fully dedicated to advancing his work in the world of literature. Despite a journey filled with challenges, his spirit has inspired the artistic community and organizations, driving positive change for the younger generation in supporting art and culture. This research employs a qualitative method with narrative analysis to reveal values that reflect the personality of "Kang Acep," using the Schwartz theory framework. The research findings indicate that in the dimension of self-achievement, "Kang Acep" demonstrates competence and the ability to reach goals without prioritizing social status. Moreover, values such as creativity, innovative thinking, and a positive outlook towards others reflect his unique personality. He also remains connected to the values of religious traditions in his work and is concerned with preserving Indonesian culture. This research illustrates how the personality of "Kang Acep" influences his contributions to art and culture, resulting in positive impacts on society and future generations.